Optimalisasi Produktivitas Kerja Untuk Manajemen Program Sosial PKK di Kecamatan Kembangan Dengan Pemanfaatan AI dan Prinsip Keamanan Siber - Yusuf, Mohamad; Rushendra (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This community service program aimed to enhance the work productivity of Pembinaan Kesejahteraan Keluarga (PKK) cadres in Kembangan District, West Jakarta, through the integration of artificial intelligence (AI) technology and cybersecurity principles. It addressed critical challenges, including low digital literacy, inefficient manual administration, and limited digital marketing capabilities. The program was executed in structured phases: a needs assessment survey (January–February 2025), data identification and literature review (February 2025), training module development and delivery of AI and cybersecurity workshops (February 2025), followed by monitoring and evaluation (March 2025–June 2026), and final report publication (July–August 2025). Fifty PKK cadres participated in the training. Results showed that 85% adopted digital systems using Google Drive and spreadsheets, reducing data loss risk by 90% and accelerating monthly reporting by 50%. Additionally, 65% utilized digital marketing platforms, with 40% of supported micro-enterprises reporting a 20% revenue increase. Evaluation revealed a knowledge score improvement from 45 to 82, with 80% of cadres proficient in digital tools and 70% effectively applying AI—without any data breaches. The initiative improved administrative efficiency, business competitiveness, and digital literacy while promoting community participation through a Merdeka Curriculum-based approach. It established a sustainable, replicable model for community empowerment applicable to other regions